Sağlık Bilimleri ve Yüksekokullar için İnsan Fizyolojisi - Yıldız Taşkıran, Sacide; Gölgeli, Münire Hande; Yazgan Özdıraz, Kamile; Küçük, Ayşegül; Savran, Özgür Yıldırım; Özkul, Tuba; Çakır, Murat; Çomu, Faruk Metin; Gündüz Başçıl, Seda; Özdemir, Ercan; Karabulut, Sebahattin; Bakkaloğlu, Umut; et al. (Academician Publishing Book DOI Portal, 2023)
-